Splitting steam via eutectic molten hydroxide assisted electrolysis for hydrogen gas production - Al-Shara, Nawar Kader Augla (2018)
In recent years, the development of hydrogen gas production from renewable energy sources has become a major area of focus to cover the shortfalls in demands of global energy. The development of water electrolysis can be considered as a promising technique in this regard for increasing the production of hydrogen fuel to meet energy requirements.